The Common Intermediates of Oxygen Evolution and Dissolution Reactions during Water Electrolysis on Iridium - Kasian, Olga; Grote, Jan-Philipp; Geiger, Simon; Cherevko, Serhiy; Mayrhofer, Karl (Angewandte Chemie International Edition, 2018)
Understanding the pathways of catalyst degradation during the oxygen evolution reaction is a cornerstone in the development of efficient and stable electrolyzers, since even for the most promising Ir based anodes the harsh reaction conditions are detrimental. The dissolution mechanism is complex and the correlation to the oxygen evolution reaction itself is still poorly understood. Here, by coupling a scanning flow cell with inductively coupled plasma and online electrochemical mass spectrometers, we monitor the oxygen evolution and degradation products of Ir and Ir oxides in situ. It is shown that at high anodic potentials several dissolution routes become possible, including formation of gaseous IrO3. On the basis of experimental data, possible pathways are proposed for the oxygen-evolution-triggered dissolution of Ir and the role of common intermediates for these reactions is discussed.
Keywords: electrochemical mass spectrometry; iridium dissolution; oxygen evolution reaction; reaction mechanisms; water electrolysis